2020
DOI: 10.1016/j.gendis.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of the computer-assisted internal fixation of a femoral neck fracture

Abstract: The number and spatial configuration of the screws will affect the stability and prognosis of the fractures. In our study, we assessed the biomechanical effects of the double-head cannulated compression screw (DhCCS) and ordinary cannulated compression screw (OCCS) for the treatment of femoral neck fractures by using computer finite element analysis. The original digital imaging and communications in medicine (DICOM)data of a proximal femur were imported into Materialise's interactive medical image control sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…This study showed that the fracture end displacement of the positive buttress group was smaller than that of the negative buttress group under the same load, that is, the stability was better. In addition, the object will produce a certain deformation under the action of external force, and the degree of deformation is called strain [ 31 ]. The mean stress of the calcar was greater in the negative group than in the positive group, showed that positive reduction or anatomical reduction can well restore normal stress conduction in the hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that the fracture end displacement of the positive buttress group was smaller than that of the negative buttress group under the same load, that is, the stability was better. In addition, the object will produce a certain deformation under the action of external force, and the degree of deformation is called strain [ 31 ]. The mean stress of the calcar was greater in the negative group than in the positive group, showed that positive reduction or anatomical reduction can well restore normal stress conduction in the hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…The stress in the horizontal group is more distributed in the screws than in the vertical group. DhCCS has reliable stability for the detection of femoral neck fractures [22]. In a study by Zhang et al [23], 24 artificial femur bones were analyzed as 3 groups.…”
Section: Resultsmentioning
confidence: 99%
“…DhCCS is recommended to treat femoral neck fractures. If the femoral neck is small, two horizontal fixations may be preferred [22]. In the study by Zhang et al showed that using one OCCS + two HCCS for the treatment of vertical femoral neck fractures outperformed using OCCS alone [23].…”
Section: Discussionmentioning
confidence: 99%
“…Femur computed tomography (CT) data were obtained from a 26-year-old male object using a Siemens 64-row CT scanner with a layer thickness of 0.7 mm were obtained. The CT image was stored in DICOM format and was outputted to the three-dimensional reconstruction medical software Mimics 21.0 (Materialise, Belgium) [ 17 ]. A three-dimensional model of the femur was built on the basis of the gray value of the tissue and segmentation of the region and then exported in stereolithography (STL) format.…”
Section: Methodsmentioning
confidence: 99%